2020
DOI: 10.1002/cyto.a.24284
|View full text |Cite|
|
Sign up to set email alerts
|

OMIP 072: A 15‐color panel for immunophenotypic identification, quantification, and characterization of leukemic stem cells in children with acute myeloid leukemia

Abstract: This panel was designed to identify, quantify and phenotypically characterize putative leukemic stem cells (LSCs) in bone marrow (BM) samples from individual pediatric patients diagnosed with acute myeloid leukemia (AML). Based on an aberrant expression on immunophenotypically defined hematopoietic stem cells (HSCs), several antigens have been proposed as LSC markers in AML research, using healthy adult BM samples as reference material. Generally, these antigens have been evaluated individually in smaller pane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Similar to our study, Petersen et al have demonstrated variant subpopulations of LSCs based on differential expression of LSC markers CD123, CD45RA, TIM3, CD25, CD93 and IL1RAP 39 . Intra‐patient heterogeneous subpopulations of LSCs were observed in 4.6% of AML samples in our study by MFC.…”
Section: Discussionsupporting
confidence: 90%
“…Similar to our study, Petersen et al have demonstrated variant subpopulations of LSCs based on differential expression of LSC markers CD123, CD45RA, TIM3, CD25, CD93 and IL1RAP 39 . Intra‐patient heterogeneous subpopulations of LSCs were observed in 4.6% of AML samples in our study by MFC.…”
Section: Discussionsupporting
confidence: 90%
“…However, multiple other LSC markers have been described, including CD123, CD7, and CD19 [ 15 , 23 , 63 ]. Due to the considerable heterogeneity between and within AML samples [ 30 ], we refrained from following a one-tube approach as performed by Zeiljemaker et al [ 22 , 63 ], where multiple LSC markers are placed in a single channel. While some LSC markers have a clear boundary between positive and negative populations (e.g., CD7, CLEC12A, and CD45RA), others may show continuous expression levels and/or overexpression compared with healthy cells (e.g., CD33, CD47, and CD96) [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, considerable immunophenotypic heterogeneity exists, and no single marker identifies all LSCs across AML samples [ 5 , 28 ]. For example, Petersen et al detected 50 LSC subsets showing 41 different immunophenotypic profiles within BM samples from 38 pediatric AML patients [ 29 , 30 ]. Also, the absence of an LSC marker on AML stem cells does not necessarily equal absence of disease, as shown by Bill et al demonstrating disease-related aberrancies within CLEC12A − stem cell subsets from AML cases [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cryopreserved BM MNCs were thawed and stained as previously described (Data S2) (Table SI). 47 Data were acquired on an LSRFortessa flow cytometer equipped with four lasers (violet, 405 nm; blue, 488 nm; yellow/green, 561 nm; red, 640 nm) (BD Biosciences). As compensation controls, single stained beads (UltraComp eBeads™; ThermoFisher) and cells were used for monoclonal antibodies (MoAbs) and the viability marker, respectively.…”
Section: Methodsmentioning
confidence: 99%